PENGARUH MULTIMEDIA PEMBELAJARAN INTERAKTIF BERBASIS GOOGLE SITES TERHADAP MINAT BELAJAR IPA SISWA KELAS V SDN 14 PALEMBANG - Suci Aprilia; M. Taheri Akbar; Arief Kuswidyanarko (Jurnal Binagogik, 2025)
This study aims to determine the effect of using interactive learning multimedia based on google sites on the learning interest of fifth grade students of SDN 14 Palembang. The background of the low interest in learning science students The type of research used is quantitative with the Quasi Experimental Design method. With Posttest-only control design. The population of this study was class V of SD Negeri 14 Palembang. The sample was class V.A which amounted to 35 students and V.B which amounted to 35 students. The data collection techniques were questionnaires and documentation. The research instrument testing technique uses validity, reliability. Based on the results of the questionnaire of interest in learning by using interactive learning multimedia based on google sites, it can be seen that the results of the questionnaire of interest in learning of experimental class students are 88.6%. While the questionnaire results of student interest in learning the control class is 59.2%. The data analysis technique in the study was processed using the normality test obtained a sig value of 0.200> 0.05 for the experimental class, and 0.121> 0.05 for the control class score. Furthermore, the homogeneity test is a sig value of 0.284> 0.05, and the Pairedt Sample T-Test test obtained a sig value. (2-tailed) of 0.000 < 0.05. So it can be concluded that Ha is accepted, meaning that there is a significant effect of using interactive learning multimedia based on google sites on the interest in learning science of fifth grade elementary school students.